(untitled) (Applied Biological Research, 2023)
The practice of discarding Umbilical Cord Blood (UCB) is very common in 3rd world countries but still a major issue in developing countries like India. UCB transfusion is done in post-Covid patients to treat anaemia, and there are various ethical issues which have to be mitigated. In this study we compared the clinical symptoms of people who received UCB for the treatment of anaemia and the people who received other standard of care for anaemia after post-Covid 19 infections. All patients were diagnosed as Covid-19 by RT-PCR test results. Symptomatic patients with complete blood count report suggestive of anaemia were included in our study. UCB was collected aseptically from surgical operation theatre. Available group matched patients were selected for transfusion after taken proper consent. All patients were followed up for consecutive four months. Results showed that the patients with cord blood transfusion recovered earlier than the patients managed by standard of care.